Peran Guru dalam Budaya Sekolah Untuk Membentuk Sikap Disiplin Peserta Didik - Natalia, Vira; Damai, Damai (Pusat Kajian Bahasa Daerah & Budaya, 2024)
Discipline reflects an attitude that embodies an awareness of and adherence to rules, contributing to the formation of moral character. As such, discipline is a critical issue, particularly in educational settings. In this context, the role of teachers in schools is crucial for developing strong character in students. This study aims to: (1) analyze the role of teachers in cultivating the disciplinary attitudes of second-grade students in class II-A at SDN-4 Menteng Palangka Raya, and (2) identify the factors that support the development of these disciplinary attitudes. To achieve these objectives, a qualitative approach with a descriptive research design was employed. The primary instrument in this research was the researcher, and data collection techniques included observation, interviews, and documentation. The data were processed through reduction, explanation, and conclusion drawing. The findings of the research indicate that: (1) The role of teachers in shaping the disciplinary attitudes of class II-A students at SDN-4 Menteng Palangka Raya encompasses their roles as educators, guides, and motivators. (2) The factors supporting the development of a disciplined attitude among these students include fostering good habits such as proper manners, time management, and adherence to rules, as well as providing consistent guidance, which collectively contribute to the enhancement of student discipline.